Side-hustle dalam Dinamika Kemiskinan Pekerja: Tinjauan Empiris di Indonesia - Natalia, Christiayu; Putranto, FX Gugus Febri (UI Scholars Hub, 2025)
Working poverty remains a persistent issue in Indonesia. The high prevalence of working poor underscores the urgent need for effective poverty alleviation efforts. This study analyzes the relationship between side hustles, excessive working hours, and working poverty in Indonesia. Utilizing microdata from the March 2023 Susenas and applying binary logistic regression, the study assesses the effect of side hustle status and excessive working hours on the likelihood of being categorized as working poor, based on the international working poverty line. The results indicate that engaging in a side hustle without excessive hours actually increases the risk of working poverty, while side hustles with excessive working hours reduce that risk. These findings suggest that side hustles are only effective in alleviating poverty when performed with excessive hours, a condition that may further exacerbate worker vulnerability. This study implies the need for policies focused on improving job quality, regulating working hours, and providing social protection for individuals engaged in side hustles.